Determining Factors in Purchasing Decisions - Iskandar Ahmaddien (Kusuma Negara Business School, 2020)
The Research aims to find out how much quality products, prices, and locations affect consumer buying decisions in the Insurgent Store. The type of research used is to use the SPSS 26 system with a model of multiple linear regression. For data retrieval in this research using qualitative method through the questionnaire and the population taken is as many as 100 respondents who are the consumers who have visited the Insurgent Store. This study include product quality (x1), Price (x2), location (x3) and purchase decision (Y). Product quality variables have the greatest impact on purchase decisions of 0908, followed by a location variable of 0888, while price variables have the lowest influence over other variables of 0872. Through this study from 3 variables used showed simultaneous influence in the visit decision making.